Constraints of Reading for Professional Context Courses Online Class During the Covid-19 Pandemic - Prastanti, Afria Dian (LPPM Universitas Pekalongan, 2022)
AbstractThe Covid-19 pandemic that hit the world in early 2020 has caused impacts on various aspects of life, including the education system. Concerning this pandemic, the Indonesian government has issued policies to regulate the learning system so that it can continue running well. One of them is the existence of a distance learning policy or online learning for all levels of education. Learning activities are carried out from home online. Online learning is considered one of the best solutions during a pandemic. However, in practice, there were constraints faced by both students and teachers. The constraints that arouse in online lectures, especially in the Reading for Professional Context course were time, internet network, internet cost, and technological facilities. These obstacles have bad impacts on the discussion process and the comprehension process of the material. These constraints and impacts are expected to be the initial part to develop strategies that can support online learning effectively. Keywords: Constraints, Reading for Professional Context, Covid-19 Pandemic